Phytochemical Profile of Urtica dioica L. by Gas Chromatography-Mass Spectrometry GC-MS and Antioxidant Activity - Alanbari, Aseel K.; Alddin, Ragha Safaa; Mohammed, Wurood Khald (Nabatia, 2025)
Leaves are rich in many phytochemical compounds, all bioactive compounds formed normally during plants metabolism as secondary products. The phytochemical compounds screened by gas chromatography-mass spectrometry (GC-MS) method. Twenty nine bioactive phytochemical compounds were identified in the . The GC-MS analysis of U. dioica revealed the identification of phytochemical compounds is based on the peak area, retention time ., as well as the antioxidant activities of the leaves were determine. . the first compound was benzene that presence at 5.339 min with peak area 1.18, while the 9-Octadecenamide was the last compound shown at 68.304 min with 2.18 peak area. Including organic compounds, fatty acids and phenols. A DPPH radical scavenging e results showed U. dioica extract at 600 concentrations high than ascorbic acid was93.76 µg/ml while aceorbic acid was 91.14 µg/ml. this finding indicate that U. dioica have high antioxidant ability. . This manuscript to cover the chemical composition of methanolic extract of U. dioica leaves ( stinging nettile) that growing naturally in Iraq, as a chemical study and provide details of pharmacological propos